Satyra jako wyzwanie dla interpretatora - Sidoruk, Elżbieta (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
The problem of low interest of Polish literary scholars in the satire is discussed in the article. The author points to the need for a deeper reflection on this phenomenon, aimed at restoring the term “satire” as necessary neutral for effective use in the analytical-interpretative practice. Taking into account the autocratic potential of satire, the author suggests to look at it as a form of challenge to the reader, which provokes the search for a “new perspective”.